Endoscopic lumbar decompression: a single-centre 40-case retrospective series - Agarwal, Dev R.; Juneja, Johney; Pathak, Lalit; Khandelwal, Shubham (International Journal of Research in Orthopaedics, 2025)
Background: Endoscopic lumbar decompression is a minimally invasive technique with advantages of reduced blood loss, shorter hospital stays and early mobilisation compared to conventional open procedures. This study reports outcomes of 40 patients who underwent lumbar endoscopic decompression at a single tertiary care center. Methods: Retrospective review of 40 consecutive patients with lumbar disc herniation or spinal stenosis who underwent endoscopic decompression. Clinical outcomes were measured using Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI) pre-operatively and at final follow-up. Operative time, blood loss, hospital stay and complications were recorded. Results: The mean age was 52 years (range 30–72), with 24 males and 16 females. The most common level was L4–L5 (60%). Mean VAS for leg pain improved from 8.1 to 2.1 (p<0.001) and ODI improved from 62% to 18% (p<0.001). Complications included 2 dural tears and 1 superficial wound infection. No revision surgeries were required. Mean hospital stay was 1.8 days. Conclusions: Endoscopic lumbar decompression is a safe and effective technique for carefully selected patients, providing excellent pain relief, functional recovery and reduced morbidity.